Formation of marketing strategies for industrial enterprises in the context of intensified competition (Economics and region, 2025)
Formation of marketing strategies for industrial enterprises inthe context of intensified competition
Keywords: marketing strategy; industrial enterprises; SWOT analysis; PEST analysis; marketing tools